2021
DOI: 10.1057/s41287-021-00431-y
|View full text |Cite|
|
Sign up to set email alerts
|

Financial Inclusion and Household Welfare: An Entropy-Based Consumption Diversification Approach

Abstract: State-led financial inclusion programmes have been implemented in many developing countries, but their effectiveness in raising welfare remains widely debated. In this article, we report evidence on this issue, against the backdrop of recent policy initiatives on financial inclusion in India. We employ Theil’s entropy-based index to estimate diversification in consumption expenditure, and use this as a measure of welfare. Using household-level panel data across all regions of the country, we find evidence that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 46 publications
1
17
1
Order By: Relevance
“…It was reported that mobile money helped consumers to improve their ability to meet basic living costs and in some cases bounce back from shocks (Ahmed & Cowan, 2021; Koomson et al, 2021; Meneses et al, 2019; Munyegera & Matsumoto, 2016; N'dri & Kakinaka, 2020; Obadha et al, 2020; Peprah et al, 2020; Sakyi‐Nyarko et al, 2021). Similarly, bank account ownership and non‐formal and formal means of saving and borrowing helped households to meet basic living costs such as food and health costs (Arellano et al, 2019; Chakrabarty & Mukherjee, 2021; Dimova & Adebowale, 2018; Gyasi et al, 2019; Habyarimana & Jack, 2018; Hussain et al, 2019; Ibrahim et al, 2019; Iddrisu & Danquah, 2021; Ksoll et al, 2016; Lyons et al, 2020; Prina, 2015; Reyers, 2019; Wiersma et al, 2020). Moreover, in India and Nepal, it was reported that bank account ownership enables households to meet basic living costs and engage in social activities such as religious festivals and ceremonies (Chakrabarty & Mukherjee, 2021; Prina, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that mobile money helped consumers to improve their ability to meet basic living costs and in some cases bounce back from shocks (Ahmed & Cowan, 2021; Koomson et al, 2021; Meneses et al, 2019; Munyegera & Matsumoto, 2016; N'dri & Kakinaka, 2020; Obadha et al, 2020; Peprah et al, 2020; Sakyi‐Nyarko et al, 2021). Similarly, bank account ownership and non‐formal and formal means of saving and borrowing helped households to meet basic living costs such as food and health costs (Arellano et al, 2019; Chakrabarty & Mukherjee, 2021; Dimova & Adebowale, 2018; Gyasi et al, 2019; Habyarimana & Jack, 2018; Hussain et al, 2019; Ibrahim et al, 2019; Iddrisu & Danquah, 2021; Ksoll et al, 2016; Lyons et al, 2020; Prina, 2015; Reyers, 2019; Wiersma et al, 2020). Moreover, in India and Nepal, it was reported that bank account ownership enables households to meet basic living costs and engage in social activities such as religious festivals and ceremonies (Chakrabarty & Mukherjee, 2021; Prina, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Access to finance was also found to influence other key outcomes, such as increasing village-level wages (Fink et al, 2020), improving local output prices by inducing delayed selling (Burke et al, 2018), causing modest business creation and expansion (Angelucci et al, 2015; Banerjee et al, 2015; Meager, 2019), and increasing other expenditures (Quach, 2016). Chakrabarty and Mukherjee (2021) used the Theil’s entropy-based index to disaggregate household consumption expenditure into food and non-food items, finding that financial inclusion does not only lead to positive changes in these items, but it also creates a shift from food items to non-food items across households. In the literature, some studies such as Ofori-Abebrese et al (2020), Hidayat et al (2021), and Gupta et al (2014) used the human development index (HDI) as a measure of welfare.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent studies on welfare by Chakrabarty and Mukherjee (2021) use Theil’s entropy-based index to assess consumption expenditure diversification and use it as a way of measuring welfare. Bağçe et al.…”
Section: Literature Reviewmentioning
confidence: 99%